CREATIVITY WITHIN RESILIENCE: SME’S GREEN ORGANIZATIONAL IDENTITY TOWARDS GREEN INNOVATION CAPABILITY - Ignasius Heri Satrya Wangsa; Agustinus Purna Irawan; Cokki Cokki (International Journal of Application on Economics and Business, 2026)
Current notions of business resilience often reduce it to “business as usual,” with little regard for long-term implications. This study reinterprets resilience by surveying 400 SME owners in Palembang, Indonesia, using a PLS-SEM model to trace how Green Organizational Identity (GOI) drives Green Innovation Capability (GIC) via Green Creativity (GC). Results confirm that GC mediates the effect of GOI on GIC. Although green creativity is central to building SMEs’ green innovation capability, we also acknowledge possible external influences. Practically, firms should cultivate an internal culture of green values that stimulates creativity. Creative adoption of green practices can heighten social awareness and accelerate the shift to a sustainable economy. We therefore define resilience as “creativity within resilience”: a steadfast commitment to strengthening organizational identity so that innovation capability grows through the conduit of creativity.